Ensuring a stable wireless communication in cyber-physical systems with moving objects - Журавська, Ірина Миколаївна (Technology audit and production reserves, 2016)
The data transmission process in cyber-physical system (CFS) with wireless communication channels between cyber-physical objects (CFO) is studied in the article. In the presence of obstacles (mechanical and electromagnetic),zero direct visibility or exceeding the allowable distance between CFO (Wi-Fi communication modules of unmanned vehicles – UMV – and/or mobile devices) that need to share data, it is necessary to take measures to restore broken communication line or to stabilization of the data transmission rate. The method for regularly radio situation overriding in CFS coverage area is proposed. The stability of wireless communication is achieved by changing energy and frequency characteristics of the communication line between CFO, as well as through the use of intermediate CFO as the signal transmitters. An algorithm for performing the specified settings depending on the model of used cyber-physical components, the distance between CFO and the delay of time interval is described. The full-scale experiment in the field using real hardware and software and with the presence of electromagnetic interference has been recreated to verify the algorithm. It is shown that for certain set of initial parameters, reducing a Wi-Fi module maximum power by 50 % improves the quality of communication in almost 8 times. Assessment of changes in the data transmission rate depending on the number of retransmissions is conducted. The stability performances of data transmission rate up to 90 %are improved by transition of communication line to another frequency range with less interference and introduction of signal retransmission function using intermediate CFO. The direction of future research is dependent on trends in the market of construction materials for UMV and computer components with built-in Wi-Fi communication modules.